ANTIOXIDANT ACTIVITY AND PHOTOPROTECTIVE in vitro OF LOTION AND GEL PROCESSED WITH EXTRACT STABILIZED OF CAMU CAMU (Myrciaria dubia Kunth.) - Inocente Camones, Miguel Ángel (2014)
In this research was to evaluated the antioxidant and photoprotective capacity of a lotion and a gel made with stabilized extract of the fruits of camu camu (Myrciaria dubia Kunth). Quality controls physicochemical, microbiological and stability to normal and accelerated conditions were performed, which allowed to develop initial parameters sunscreens extract of camu camu. Antioxidant activity by DPPH and ABTS method, values of 876.729 umol Trolox/g camu camu for gel and 1389.650 umol Trolox/g camu camu for lotion was determined (DPPH method) and values of 15.330 mmol Trolox/g camu camu for gel and 23.384 mmol Trolox/g